Oncoepidemic peculiarities of population of Interial Mountain Dagestan - P. M. Rokhoeva; A. G. Gasangadjieva (Юг России: экология, развитие, 2015)
Complex ecologogeographical and socialeconomic reseach of natural and anthropologic environment components of Akhwakh, Khunzakh and Untsukul Districts of Mountain Dagestan shows the dependence between quality of the environment and dinamik of the cancer.